تعلم اللغة العربية في المدرسة الجزائرية بين الواقع والمأمول - دومان، غنية Douman, Ghaniah (جامعة العربي بن مهيدي - أم البواقي, 2022)
تطمح هذه الدراسة إلى تناول واقع اللغة العربية في المدرسة الجزائرية عبر الطورين الأول والثاني وصفا تحليلا ونقدا وذلك بمعاينة العملية التعليمية في شموليتها وعمقها. ومحاولة منا للإحاطة بكل مجالات الموضوع فقد ارتأينا دراسة كل أطراف العملية التعليمية في إطار عملية تواصلية كاملة تعبر عن الاهتمام بكل من المعلم والمتعلم والمادة العلمية من خلال رؤية شاملة محكمة. ولذا استثمرت في هذا التحليل بعض النظريات التعليمية للإحاطة بدور المعلم باعتباره عنصرا فعالا في المعادلة التعليمية. والاهتمام نفسه منصب على المتعلم الذي يضطلع بدور التلقي والتفاعل والتجاوب مع المادة العلمية المقدمة. This study aims to address the reality of the Arabic language in the first and second stages at the Algerian school. It describes, analyzes and criticizes by examining the comprehensiveness and depth of the educational process. In order to delimit all aspects of this subject, we considered the study of all the educational process parties in the context of a full communication process reflecting the interest of the teacher, the learner and the study material through a comprehensive and tight vision. Therefore, some educational theories have been used to study the teacher’s role as an effective element in the educational equation. The same attention has been paid to the learner who plays the role of receiving, interacting and responding to the presented study material.
Keywords: تعلم اللغة العربية -- المؤسسات التعليمية -- المناهج التعليمية -- الجزائر